1994
DOI: 10.1128/jb.176.8.2158-2164.1994
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of naphthalene, fluorene, and phenanthrene: preliminary characterization of a cloned gene cluster from Pseudomonas putida NCIB 9816

Abstract: A modified cloning procedure was used to obtain large DNA insertions (20 to 30 kb) from Pseudomonas putida NCIB 9816 that expressed polycyclic aromatic hydrocarbon (PAH) transformation activity in Escherichia coli HB101. Four subclones (16 [in both orientations], 12, and 8.5 kb in size) were constructed from the initial clones. Naphthalene, fluorene, and phenanthrene transformations were investigated in these eight NCIB 9816 clones by a simple agar plate assay method, which was developed to detect and identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…Overall, the broad PAH-degrading capabilities in many strains may be attributed to relaxed initial enzyme specificity for PAHs (low and high molecular weight and methyl substituted), the presence of multiple oxygenases, and the presence of multiple metabolic pathways or multiple genes for isofunctional pathways (83,112,160,249,220,330,396,399,418,437,519,520,532,641,677). Finally, the presence of both alkane and aromatic compound-degrading genes within single strains appears to be common (120,301,576,578,641,662).…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%
“…Overall, the broad PAH-degrading capabilities in many strains may be attributed to relaxed initial enzyme specificity for PAHs (low and high molecular weight and methyl substituted), the presence of multiple oxygenases, and the presence of multiple metabolic pathways or multiple genes for isofunctional pathways (83,112,160,249,220,330,396,399,418,437,519,520,532,641,677). Finally, the presence of both alkane and aromatic compound-degrading genes within single strains appears to be common (120,301,576,578,641,662).…”
Section: Aerobic Pah Metabolismmentioning
confidence: 99%
“…A useful chromogenic property of several of these enzyme systems is the ability to oxygenate the heterocyclic ring of indole, facilitating indigo formation (17). This property has been valuable in the cloning of aromatic hydrocarbon dioxygenase genes (10,11,16,29,30,45) and in the development of processes for the industrial production of indigo (32).Dioxygenase reactions leading to 1,2-diphenol formation and ring cleavage are also employed by bacteria in the catabolism of a number of aromatic carboxylic acids. This is the case for compounds such as benzoic acid (35, 36), phthalic acid (2, 15, 38), phenylpropionic (hydrocinnamic) acid (4, 42), m-and p-toluic acids (1, 43), and p-cumic acid (8).…”
mentioning
confidence: 99%
“…A useful chromogenic property of several of these enzyme systems is the ability to oxygenate the heterocyclic ring of indole, facilitating indigo formation (17). This property has been valuable in the cloning of aromatic hydrocarbon dioxygenase genes (10,11,16,29,30,45) and in the development of processes for the industrial production of indigo (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymatic steps for the decomposition of the first and second rings of phenanthrene in the salicylate route resemble those of the first ring of naphthalene. It has been demonstrated that a common set of enzymes was responsible for the decomposition of the first and second rings of phenanthrene, as well as for the first ring of naphthalene (26,34,36). The PAH-degrading pathway via salicylate found in Burkholderia cepacia F297 seems to exhibit quite broad substrate specificity, as this pathway degrades a wide variety of polycyclic aromatic compounds, including fluorene, (methyl-)naphthalene, phenanthrene, anthracene, and dibenzothiophene (12).…”
mentioning
confidence: 99%